Measuring Contingency Factors in the Application of Knowledge Management in the XYZ College Session Management System Process - Aulia Faradilla Jasmine; Ida Nurlela; Jenyta Primaranti; Satria Valerian Shari; Riya Widayanti (SMART : Jurnal Teknologi Informasi dan Komputer, 2024)
The phenomenon of knowledge management can be seen as a desire to restore the essence of "knowledge" and avoid the view that knowledge is an inanimate object. In organizational life, both for business and non-business, knowledge is always associated with the potential value that exists in various components or processes (flows) of the overall "capital" in the organization. In knowledge management, contingency factors refer to various conditions and situations that can influence the design and implementation of an organization's knowledge management system. By understanding these factors, an organization can adapt its knowledge management strategy to meet their unique needs and characteristics. The research method used by researchers in this study is a qualitative approach using descriptive methods, using descriptive-qualitative methods which can be used to measure contingency factors in the application of knowledge management in the trial management system process. Assessment of knowledge management for KM solutions has helped in creating, capturing, sharing, and apply knowledge and influence the 4 aspects of individual/person/employee, product, process, and overall organizational performance. The impact of knowledge management on organizations is also very important, which includes People, Product, Process, Over All Performance. KM processes can influence organizations at four levels in two ways. First, the process can help create knowledge, which can help improve organizational performance on all four measures. The terms "final project" and "thesis" are used in higher education to refer to scientific work which is a presentation of the results of Bachelor's Degree (S1) research which discusses a problem in a particular field using applicable rules.